Comparative effects of hip capsule repair and cam lesion excision on capsulotomy healing: An in vivo biomechanical and histological analysis - Abbas Aghayev; Burak Duymaz; Selahaddin Aydemir; Pınar Akokay Yılmaz; Gurhan Tukel; Resit Bugra Husemoglu; Onur Gürsan; Onur Hapa (Journal of Experimental Orthopaedics, 2025)
ABSTRACT Purpose This study evaluates the effects of hip capsule repair and cam lesion excision on capsular healing by assessing biomechanical strength and histological integrity in an in vivo rabbit model. Methods An in vivo rabbit model with 80 rabbits was used, where capsulotomy was performed on the right hip of each subject. The rabbits were assigned into four groups: Group 1 (capsulotomy without repair), Group 2 (capsulotomy with capsule repair), Group 3 (capsulotomy + cam resection without repair), Group 4 (capsulotomy + cam resection + capsule repair). Each group was stratified into 4‐week and 8‐week follow‐up subgroups. Biomechanical testing assessed maximum tensile strength, while histological evaluation included semiquantitative grading of collagen arrangement, inflammatory response, osteogenesis, and angiogenesis. Results Histological analysis revealed superior healing in the capsule repair + cam resection group (Group 4) compared to the unrepaired capsulotomy group (Group 1) (p = 0.01). Biomechanical testing demonstrated that capsule repair (Group 2) improved strength over unrepaired capsulotomy (135.2 N vs. 111.9 N, p = 0.03). Cam resection alone (Group 3) resulted in significantly higher strength than unrepaired capsulotomy (163.2 N vs. 111.9 N, p = 0.01). The combination of cam resection and capsule repair (Group 4) demonstrated superior strength, outperforming capsule repair alone (176 N vs. 135.2 N, p = 0.01). At 8 weeks, the capsule repair + cam resection group (Group 4a) showed significantly enhanced biomechanical strength compared to the unrepaired capsulotomy group (Group 1a) (181.6 N vs. 120.9 N, p = 0.001) and capsule repair alone (Group 2a) (181.6 N vs. 125.8 N, p = 0.01). Conclusion Our findings indicate that cam resection, particularly when combined with capsule repair, significantly improves biomechanical strength and enhances the healing process of the capsule. These findings offer practical guidance for optimising surgical strategies to enhance patient outcomes and long‐term joint function. Level of Evidence Level III, experimental therapeutic study (prospective and controlled).